Análise das políticas públicas nacionais voltadas à inserção da pessoa com Trissomia-21 no mercado de trabalho - Nascimento, Jhule Michele Lopes (Universidade Federal do Tocantins, 2021)
The present work sought to verify the public policies that protect the insertion of the person with Trisomy 21 in the job market. Given the approached theme, it has been sought to describe the condition of the person with Trisomy 21, it has been researched the legislation in the country's juridical order and its impacts on the rights of the people with Trisomy 21 and it has been analyzed the Public Policies directed to the insertion in the work market for people with Trisomy 21. This way, bibliographies, laws, legal and historical documents that support the implementation of inclusive measurements for people with Trisomy 21 (Down Syndrome) in the labor field have been researched, and the effectiveness and efficiency of the implemented measurements have been analyzed. It can be noticed, according to the data collected, the inexistence of measures specifically aimed at the inclusion of the person with Trisomy 21, as a person with intellectual disabilities, in the labor field.